Interfacial interactions of iron(II) tetrapyrrole complexes on Au(111) - Schmid, Martin; Zirzlmeier, Johannes; Steinrück, Hans-Peter; Gottfried, J. Michael (Journal of Physical Chemistry C, 2011)
The electronic structure of monolayers of iron(II) phthalocyanine (FePc), iron(II) octaethylporphyrin (FeOEP), and iron(II) tetraphenylporphyrin (FeTPP), adsorbed on Au(111), was examined with X-ray and UV photoelectron spectroscopy (XPS/UPS). Comparison of the Fe 2p signals of FePc multilayers and monolayers revealed an additional component in the monolayer signal with a binding energy characteristic of Fe(0). This component accounts for ∼20% of the integral Fe 2p intensity, in agreement with previous observations on cobalt porphyrins on Au(111). The partial modification of the Fe 2p states suggests a laterally inhomogeneous interaction of the adsorbed molecules with the metal surface and is possibly related to the complex, reconstructed Au(111) surface morphology. Similar results obtained for FeTPP and FeOEP monolayers indicate that this effect is independent from the structure of the peripheral substituents on the core porphin moiety. The UP spectra of FePc and FeTPP monolayers show further indications for a substrate-molecule interaction mediated by the central Fe atom. In addition, FePc, FeTPP, and 2HTPP monolayers lead to a complete depopulation of the Shockley surface state of the clean Au(111) surface. © 2011 American Chemical Society.